Between giants and windmills: Lulismo in the presidential elections of 2018 - Mércia Alves; Joyce Miranda Leão Martins (Íconos)
Lulismo, as a broad phenomenon of adhesion to the political figure of Luiz Inácio Lula da Silva, is also based on the approval of the image of “man of the people,” which was mobilized in the 2002 elections and continuously evoked against the Brazilian Social Democratic Party. In this article, we analyze the electoral propaganda strategies of the Workers’ Party at a time when its major leader was imprisoned and its main opponents were others: the “dragons” of anti-petismo. Based on the fact that television continues to be important in the Brazilian electoral game, the corpus of the analysis is the electoral television calendar of the Workers’ Party during the first and second rounds. The methodology used combines the observation of the types of ads with the analysis of the French matrix discourse, based mainly on the contributions of Charaudeau and Orlandi. As categories, ethos and antiethos, interdiscourses, discursive formations, ideological formations, and social conditions of production are observed. It is concluded that Lulismo was mobilized to fight against the Temer government and the Brazilian Social Democratic Party, which were not dangerous rivals; however, it failed to build a narrative against the “dragons” of anti-petismo that questioned not only the Brazilian electoral game, but the democratic regime itself.